Effects of PWIM in the ESL classroom: vocabulary knowledge development among primary Malaysian learners - Lee, Bee Choo; Ambigapathy Pandian,; Souba Rethinasamy,; Tan, Debbita Ai Lin (Penerbit Universiti Kebangsaan Malaysia, 2019)
The present quasi-experimental study examined the impact of pictures, via a modified version of Emily Calhoun’s (1999) Picture Word Inductive Model (PWIM), on the English vocabulary acquisition of Malaysian Year 1 pupils in a rural national primary school. Meara and Buxton’s (1987) Yes-No Recognition Test (YNRT) was adapted and further tested for reliability to measure the recall and retention of subjects’ vocabulary size. A total of 60 subjects participated in the research, comprising two intact classes; one class formed the Experimental group and the other formed the Control group. The former underwent the intervention while the latter received typical classroom instruction. Results gleaned from independent samples t-tests revealed superior vocabulary scores at the posttest and delayed posttest levels by the Experimental group, denoting greater vocabulary knowledge recall and retention that reflects the effectiveness of the intervention in enhancing vocabulary acquisition among young Malaysian learners. This study and its findings are of significance to English language teachers, curriculum designers, policy makers, and scholars engaged in ESL/EFL research. It is also noteworthy that there exists a paucity with regards to in-depth research on the use of images for language learning among young learners, particularly within the Malaysian context.